Oral hygiene habits and prosthodontic treatment needs in younger adolescent population of Pančevo, Serbia - Pavlovic, Maja; Jevremovic, Danimir; Matijevic, Dusanka; Vukovic, Branislava; Borotic, Nenad; Jevremovic, Ana; Tambur, Zoran; Lazic, Srdjan (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Dental status and oral hygiene habits are poor in young population living in deprived socioeconomic conditions. The aim of this research was to ascertain oral hygiene habits in adolescents attending high schools in urban area, determine the incidence of tooth loss at the age of 15–16 years and the gender difference. Methods. The epidemiological cross-sectional study included 234 randomly selected high school students. The research instruments were questionnaire (focusing on socio-demographic characteristics, habits, attitudes and behavior related to general and oral health) and clinical examination (tooth loss, normative need for prosthodontics restorations and presence of restorations). Results. Gender-related data comparison revealed that 32.5% of girls and 8.1% of boys had at least one tooth extracted (p
Keywords: adolescent; dental care; dental health surveys; dentures; habits; oral hygiene; tooth extraction